Combined Effects of Microplastics and Biochar on the Removal of Polycyclic Aromatic Hydrocarbons and Phthalate Esters and Its Potential Microbial Ecological Mechanism - Ren, Xinwei; Tang, Jingchun; Wang, Lan; Sun, Hongwen (Frontiers in Microbiology, 2021)
Microplastics (MPs) has been attracting wide attention. Biochar application could improve the soil quality in the contaminated soil. Currently, most studies focused on the effect of MPs or biochar on the soil properties and microbial community while neglected their combined effects. This study investigated the combined effects of biochar (BC) or ball-milled biochar (BM) and polyethylene plastic fragments (PEPF) and degradable plastic fragments (DPF) on the removal of polycyclic aromatic hydrocarbon (PAHs) and phthalate esters (PAEs) in the PAHs contaminated soil and the potential microbial ecological mechanisms. The results showed that BC or BM combined with PEPF could accelerate the removal of PAHs and PAEs. PEPF combined with BM had the most significant effect on the removal of PAHs. The potential mechanism might be that BM increased the abundance of Methylophilaceae, Bacillaceae, Burkholderiaceae and Bogoriellaceae which could act as the PAHs degrading microorganisms. PEPF and BM increased the abundance of Nectriaceae family and some of the microbes in this family played the key role in the removal of PAHs. It is suggested that selection effect on the microbial community by biochar and microplastic played key role on the degradation of PAHs and PAEs in soil.